The Kannada Mahabharata - Kumāravyāsa (Harvard University Press, 2024)
"Volume 1 comprises "The Book of Beginnings" and "The Book of the Assembly," including Pandu's tragic death, the marriage of the Pandavas to Draupadi, Arjuna's fiery destruction of the Khandava forest, the slaying of King Shishupala, and the dice game plotted by the Kauravas leading to the Pandavas's exile. This edition, which abridges the Kannada classic, presents a new English translation and the most reliable text of the original in the Kannada script."
Author's name also appears on the title page in Kannada script: "Kumāravyāsa"
Includes bibliographical references and index